Numerical modeling techniques and investigation into the flexural behavior of two‐way posttensioned concrete slabs with profiled steel sheeting. (7th November 2022) - Dinh, Phuoc Tho; Doh, Jeung‐Hwan; Fragomeni, Sam; Ho, Nhat Minh; Peters, Tim
Abstract: In recent years, the combined use of posttensioning methods with steel decking in the concrete slabs has provided significant benefits in both economic and structural terms. In construction practice, this prestressed composite floor has extensive use in two‐way spanning slab systems. However, this application still has inherent limitations due to its novelty and lack of research in this specific field. Hence, this study aims to gain the first insight into the flexural behavior of a two‐way posttensioned composite (PTC) slab system based on a numerical approach. Scientific software is utilized for the derived model validation with a focus on models' geometric and material nonlinearity. Available modeling techniques used to perform the posttensioning process and interaction of composite slabs are verified with existing experiments. A comparative study was conducted between PTC slabs and various conventional slab systems on two different support conditions. The findings in this study consider the structural effects of posttensioning and profiled steel sheeting on the flexural behavior of PTC slabs. In addition, numerical results from this research might help structural engineers to modify the design input parameters and make judgments on the bending stiffness of this two‐way slab structure. Further studies are required since the shear behavior, flexural, and punching shear conditions in the column regions are not addressed in this article.